Issues in Underwater Cultural Heritage Impact Assessments in China. Issue 6 (2nd November 2019) - Lin, Zhen
Abstract: During the past decades, the number of coastal and marine construction projects has multiplied in China, posing a serious threat to underwater cultural heritage in its waters. In contrast, there are few rules dealing with underwater cultural heritage impact assessment which has not yet become a mandatory procedure in various coastal and marine construction projects. With China putting forward the Belt and Road Initiative, the conflicts between the protection of underwater cultural heritage and the need of various coastal and marine construction projects might become more frequent. Chinese legislation in this domain, undergoing important revision, intends to establish a mandatory procedure of proactive archeological investigation. This revision could have a great influence on the protection of underwater cultural heritage as well as the coastal and marine construction projects in China but the relevant provisions are still far from satisfactory. The present study will review the current Chinese legislation concerning the impact assessment of marine or coastal construction projects on underwater cultural heritage and explore the possibility for further improvement at the legislative level.